Prognostic value of socioeconomic parameters among the Russian population aged 25-64: results of a population-based study - A. E. Imaeva; Yu. A. Balanova; L. I. Gomanova; V. A. Kutsenko; N. A. Imaeva; B. M. Nazarov; A. V. Kapustina; S. E. Evstifeeva; G. A. Muromtseva; S. A. Shalnova; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2025)
Aim. To assess the contribution of individual socioeconomic parameters to the risk of death and cardiovascular events among Russian men and women aged 25-64, according to epidemiological study data.Material and methods. The study was based on data from the prospective study ESSE-RF (2013-2014) and ESSE-RF2 (2017), which included a total of 22812 participants aged 25-64 years from 14 regions. The analysis assessed the following sociodemographic parameters: marital status, education level, income, employment, and type of settlement. From 2013 to 2021, 688 participants died. The composite endpoint (CE), including fatal and non-fatal (myocardial infarction and/or cerebrovascular accident) cardiovascular events, was registered in 470 (4,6%) men and 380 (2,4%) women. Associations with endpoints were assessed using Cox proportional hazards models with corresponding hazard ratios (HR).Results. According to multivariate analysis, the following parameters were significantly associated with the all-cause death risk in the male population: non-marriage (HR 1,86, 95% confidence interval (CI): 1,48-2,33), no higher education (HR 1,34, 95% CI: 1,08-1,67), low income (HR 1,32, 95% CI: 1,06-1,63), non-employment (HR 1,97, 95% CI: 1,58-2,46); with CE — no higher education (HR 1,64, 95% CI: 1,34-2,01), nonemployment (HR 1,49, 95% CI: 1,21-1,84). In the population of women, a reliable contribution to all-cause death risk and CE occurrence was made by the lack of higher education and non-employment — HR 1,54, 95% CI: 1,17-2,04; HR 1,64, 95% CI: 1,26-2,14; HR 1,35, 95% CI: 1,07-1,71; HR 1,38, 95% CI: 1,1-1,73, respectively.Conclusion. The study results indicate that the most unfavorable prognostic factors in relation to death risk and fatal and non-fatal cardiovascular events are the lack of higher education and nonemployment, regardless of sex and region of residence.